Evaluación de la satisfacción laboral y su contribución al desempeño empresarial en la empresa de lácteos REYVER S.A. - Burgos Burgos, Ángel Winer (2017)
The research, evaluation of job satisfaction in the company Reyver S.A., aimed to diagnose the state of the organization in order to contribute to business performance, for which I pose as a premise, if the variables analyzed would generate reliable results; Regarding the applied procedure, it required an analytical-synthetic methodology, based on qualitative-quantitative results, a work scheme based on four phases was proposed; where the variables were determined in the first instances, by means of a group of experts that served as support for its validation, in this stage it was required to apply the Kendall bibliographic research and methodology; after that, the evaluation tool model validated by the work team was structured, in order to apply it together with an interview addressed to the manager; the data obtained were tabulated and presented by statistical tools; In Phase 3, the SPSS Software established a correlation between the variables, with the purpose of analyzing the internal consistency using the Cronbach's Alpha, in order to determine the company's situation and propose corrective actions through the matrix 5W + 1H. The results show that the instrument applied to the organization presents acceptable results in the variables investigated, however, the participation of the workers and the acknowledgments are signs that it is necessary to optimize certain areas, since the perception of Human Talent is not unanimous, leaving glimpsed personnel not satisfied with the current performance of the organization.